FEATURES OF WORKING CONDITIONS OF EMPLOYEES IN THE TASHKENT METROPOLITAN (Eureka Journal of Health Sciences & Medical Innovation, 2025)
The relevance of the research topic is determined by the need for comprehensive modernization and restructuring of transport networks and transport infrastructure through the formation and development of transport hubs that ensure the most effective interaction of all elements of the transport system. The primary objective of passenger transport is to fully meet the public's transportation needs. Transportation is one of the most pressing challenges facing large cities and metropolitan areas, and with their growth and development, it is becoming increasingly pressing socially, urbanistically, and economically.
Keywords: Working conditions, hazardous production factors, noise, vibration, microclimate, subway.